Diferensiasi Teori Common Link G.H.A Juynboll dan Tradisi ‘Ulum Al-Hadis Klasik dalam kasus Sanad Hadis Wanita Kurang Akal - Khairul Amin; Aisyah Chairil (Program studi Keagamaan Islam, 2022)
This article tries to disscuss the application of G.H.A Juynboll common link’s theory and Isnad convetional criticize (‘Ulum Al-Hadis) The application of critical theory of Isnad do in comparative analysze frame. The issue used as an object of the study is the hadith on women’s lack of reason which finding on kuttub al sittah or six primary books on hadith. The hadith is quite tendentious or can be categorized as misogynistic hadith from a gender perspective (feminism), on the contrary, Muslim scholars have provided adequate rebuttals and explanations to this attack. Anyway, this research is limited to isnad criticism only, does not touch on the hadith matan especially on its meaning exploration or debates. The final result is about the hadith’s authenticity status based on isnad which is based on different methodology of each scholarship.